Perdagangan Internasional: Tinjauan Pustaka tentang Manfaat, Dampak, dan Kebijakannya - Manalu, Jhon Kristopel; Remus Silalahi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
No country can live alone. This is due to the limitations of the resources it possesses. Therefore, a country will need other countries. In order to fulfill their needs, every country engages in trade relations. This trade relationship between countries is also called international trade. Why does every country engage in international trade? Because by engaging in international trade, many benefits are obtained, although there are also losses that will be incurred. Each country also has its own policies to protect their domestic economy from the negative impacts of competition arising from international trade. International trade allows the entry of goods and services from abroad into the country. If goods and services from abroad are more abundant and more in demand by the public compared to domestic products, then this will have a negative impact on the domestic economy. Therefore, the government needs to formulate an international trade policy.